Hydrocarbon tolerance evaluation of the microbiota associated with the Roystonea oleracea palm from Santay Island (Ecuador) - Andrade, Jean Carlo; Santiago Mafla; Kelly Riofrío; José Hernández; Tobes, Ibon; Cristian Lara-Basantes (My University, 2024)
Soil contamination from hydrocarbon spills has resulted in significant environmental repercussions on a global scale. Bioremediation, which involves the use of living organisms such as microbes to remove contaminants from polluted ecosystems, offers a promising solution. In this study, tolerance tests on hydrocarbons present in Jet Fuel A1 were carried out, utilizing microorganisms isolated from four soil samples (M1, M2, M3, and M4) collected at varying distances from the rhizosphere of Roystonea oleracea on Santay Island, a RAMSAR wetland located in the Guayas River estuary on the Pacific coast of Ecuador. Sample M1 was closest to the base of the palm, while M4 was the farthest. Various soil ions, including potassium, phosphates, iron, and total nitrogen, were analyzed, and higher concentrations were found near the base of the palm. Additionally, a metabolic profile analysis of the samples was conducted using Ecoplate® kits, which revealed similar trends, with carbon sources being predominantly consumed near the base. A community-level analysis was performed using Denaturing Gradient Gel Electrophoresis (DGGE), followed by molecular characterization through amplification of the 16S RNA conserved region via the Sanger method. The identified microorganisms included Lysinibacillus fusiformis, Lysinibacillus boronitolerans, Alcaligenes faecalis, and Bacillus soli in the soil samples. Notably, strains isolated from samples near the palm's base were able to grow in media enriched with Jet Fuel A1 and demonstrated the ability to produce biosurfactants, as determined by the drop-collapsing method. The results obtained present opportunities for future research in the exploration of novel green remediation technologies.
Keywords: ADN; biosurfactants; DGGE; hydrocarbons; jet fuel; microorganisms; tolerance